Laparoscopic surgery for urachal remnants in pubescent children: a case series - Naoki Hashizume; Masahiro Ohtaki; Kouei Nihei; Kaoru Sakamoto; Yasuhiro Shirahata; Tetsuya Shimada; Eriko Ohta; Daisuke Yamai; Akihiro Takeshi; Kaito Sato; Satoshi Suzuki; Minoru Yagi (Surgical Case Reports, 2020)
Abstract Background Various techniques are applied in laparoscopic surgery for the treatment of urachal remnants, which are less invasive and associated with lower morbidity. We herein report a case series in which we treated urachal remnants and medial umbilical ligaments using a laparoscopic approach. Case presentation From 2015 to 2019, seven patients (male, n = 5; female, n = 2) with a urachal remnant were treated by laparoscopic surgery in our institute. Five boys and two girls with a median age of 11 years (range 10–15 years) were enrolled in this series. The clinical results of laparoscopic treatment, the perioperative records, and the pathologic results were evaluated. The operation was performed with the use of three ports and an EZ access® (Hakko Medical, Nagano, Japan), which is a silicon cap for the wound retractor (Lap Protector®, Hakko Medical, Nagano, Japan). The removal of the urachal remnant and medial umbilical ligaments was completed with a median operative time of 92 min (range 69–128). The median hospital stay after surgery was 4 days (range 2–5). No patients developed intra-postoperative complications or recurrence. Conclusions Although our data are preliminary, complete laparoscopic removal of symptomatic urachal remnants and medial umbilical ligaments was a safe and effective minimally invasive approach, with better cosmetic outcomes.